Fabrication of fluorescent nanospheres by heating PEGylated tetratyrosine nanofibers - Enrico Gallo (Nature Portfolio, 2021)
Abstract Aromatic polypeptides have recently drawn the interest of the research community for their capability to self-assemble into a variety of functional nanostructures. Due to their interesting mechanical, electrical and optical properties, these nanostructures have been proposed as innovative materials in different biomedical, biotechnological and industrial fields. Recently, several efforts have been employed in the development of these innovative materials as nanoscale fluorescence (FL) imaging probes. In this context, we describe the synthesis and the functional properties of a novel fluorescent tyrosine (Tyr, Y)-based nanospheres, obtained by heating at 200 °C a solution of the PEGylated tetra-peptide PEG6-Y4. At room temperature, this peptide self-assembles into not fluorescent low ordered water-soluble fibrillary aggregates. After heating, the aggregation of different polyphenolic species generates Y4-based nanospheres able to emit FL into blue, green and red spectral regions, both in solution and at the solid state. The aggregation features of PEG6-Y4 before and after heating were studied using a set of complementary techniques (Fluorescence, CD, FT-IR, Small and Wide-Angle X-ray Scattering and SEM). After a deep investigation of their optoelectronic properties, these nanospheres could be exploited as promising tools for precise biomedicine in advanced nanomedical technologies (local bioimaging, light diagnostics, therapy, optogenetics and health monitoring).